Clinical and diagnostic virology - Kudesia, Goura (Cambridge University Press, 2024)
Since the first edition was published in 2009, there have been significant advances in diagnostics and management of viral infections, as well as newly discovered viruses such as SARS-CoV-2 and Zika virus. This new edition provides up-to-date information on the key developments in clinical and diagnostic virology, especially molecular diagnosis, with guidance on new molecular and bedside tests. Effective antiviral treatments and novel combinations of treatments recently introduced are covered in depth. Infection control precautions and pandemic preparedness are discussed, with a focus on recent outbreaks. As with the first edition, coverage is succinct and practical with easily accessible information in algorithms and tables, and standardised chapter layouts organised from A to Z. This is an ideal introduction to complex topics for healthcare trainees, as well as a handy and easily accessible reference for more experienced hospital clinicians and primary care physicians.